2020
DOI: 10.1002/dmrr.3357
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset type 1 diabetic patients with less severe clinical manifestation have less risk DR‐DQ genotypes than childhood‐onset patients

Abstract: BackgroundThe aim of this study was to investigate differences in clinical features and HLA genotypes between adult‐onset and childhood‐onset patients with type 1 diabetes in a Chinese population.Materials and MethodsThis study enrolled 716 Han Chinese patients with type 1 diabetes from Guangdong (258 childhood‐onset and 458 adult‐onset) to compare their clinical features. Of them 214 patients with classical type 1 diabetes (100 childhood‐onset and 114 adult‐onset) were selected for HLA DR and DQ genotyping by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…It has been reported that European patients with younger onset age had a higher frequency of the susceptible DRB1*03:01-DQB1*02:01/DRB1*04 -DQ8 genotype, but a lower frequency of the protective DRB1*15:01-DQB1*06:02 and DRB1*07:01-DQB1*03:03 haplotypes than those with older onset age [14]. Our previous study in Chinese patients showed that, compared with childhood-onset patients, adult-onset patients had a lower frequency of the high-risk DR3/DR4 and DR3/DR9 genotypes, but higher frequency of DR3/DR3 genotype and DR3/X, DR4/X, or DR9/X (X, non-risk) genotypes [11].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…It has been reported that European patients with younger onset age had a higher frequency of the susceptible DRB1*03:01-DQB1*02:01/DRB1*04 -DQ8 genotype, but a lower frequency of the protective DRB1*15:01-DQB1*06:02 and DRB1*07:01-DQB1*03:03 haplotypes than those with older onset age [14]. Our previous study in Chinese patients showed that, compared with childhood-onset patients, adult-onset patients had a lower frequency of the high-risk DR3/DR4 and DR3/DR9 genotypes, but higher frequency of DR3/DR3 genotype and DR3/X, DR4/X, or DR9/X (X, non-risk) genotypes [11].…”
Section: Introductionmentioning
confidence: 84%
“…The strong contributions of HLA-DR and -DQ genes to type 1 diabetes, and the extremely high LD within the HLA region emphasise the importance of adjustment or stratification for DR-DQ when analysing the effects of additional susceptibility genes. Our recent study showed that, compared with childhood-onset patients, adult-onset patients had milder clinical features and a lower frequency of high-risk DR3/DR4 and DR3/DR9 genotypes [11]. Based on our previous study, we expanded the sample size and did linear regression analyses of DR-DQ in patients through all onset ages in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects were genotyped by sequencing exon 2 of each gene yielded two‐ or four‐digit resolution for HLA‐DQA1 and four‐digit resolution for HLA‐DQB1 and HLA‐DRB1. According to the previous research, DR3 (DRB1 * 03:01:01‐DQA1 * 05:01:01‐DQB1 * 02:01:01), DR4 (DRB1 * 04:05:01‐DQA1 * 03:03:01‐ DQB1 * 04:01:01, DRB1 * 04:05:01‐DQA1 * 03:01:01‐DQB1 * 03:02:01 and DRB1 * 04:05:01‐DQA1 * 03:03:01‐DQB1 * 03:02:01) and DR9 (DRB1 * 09:01:02‐DQA1 * 03:02‐DQB1 * 03:03:02) were haplotypes associated with T1D susceptibility in Chinese 13 . Non‐susceptible haplotype was defined as DRX where x was not DR3, DR4 or DR9.…”
Section: Methodsmentioning
confidence: 95%